(untitled) (Journal of Contemporary Studies, 2022)
US-India strategic convergence is likely to continue as Washington considers New Delhi a counterweight to Beijing. However, rising right-wing authoritarianism in India under BJP, marked by the erosion of democratic standards, has created a policy paradox for Biden Administration- how to balance geopolitical interests with democratic ideals. The paper argues that adhering to the norms of democracy is not just a normative concern but also a strategic concern for the US as democracy is one of the core pillars that sustains US- led liberal world order. However, the Biden administration does not appear to emphasize democratic values and human rights performance to the point where strategic convergence would seem at risk. Thus Biden administration is likely to emphasize democratic values and human rights performance to the point where strategic convergence would not seem at risk. Keywords: Democracy, Human Rights, Balancing, US, India, China